A BIBLIOMETRIC REVIEW OF RESEARCH ON PARTICIPATIVE LEADERSHIP THEORY IN EDUCATION: SCIENCE MAPPING THE LITERATURE, 1926-2023 - Wiwin Windiana; Ega Nur Fadillah; Muhammad Iqbal Nugraha (Politeknik Siber Cerdika Internasional, 2024)
This study aims to undertake a comprehensive analysis addressing the extent, growth patterns, and geographical spread, of journals, authors, and articles that have demonstrated the most significant impact in terms of relevance. The methodology entails the use of visualization techniques and bibliometric analysis as quantitative tools and the adoption of an evaluative and descriptive approach to depict the research analysis. The data sourced from the reputable Scopus database have led to the identification of a total of 850 publications, encompassing various formats such as repositories, books, book chapters, journal articles, and proceedings. In the analysis of these publications, the study delves into the years 1926-2023, employing the R Studio and VOS Viewer software. The finding shows that North America and Europe are well-represented among the top contributors. The article's production over time highlights diverse trajectories among countries like Spain, the United Kingdom, the USA, Indonesia, and Canada. However, it's noteworthy that high productivity doesn't guarantee a similar level of citation impact. The relationship between productivity and relevance, is intricate, reflecting the dynamic nature of research impact in the academic domain. Furthermore, the analysis reveals a noticeable upward trend in the frequency of key categories such as leadership, human, article, education, and others over the specified period. Furthermore, the persistence of these trends from 2021 to 2023 signifies the enduring relevance and evolution of participative leadership research. The exploration of correlations with traditionally less associated dimensions reflects the field's adaptability and responsiveness to contemporary issues.